2014
DOI: 10.1021/ja510163w
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Anti-Markovnikov Oxidation of Allylic Amides to Protected β-Amino Aldehydes

Abstract: A general method for the preparation of N-protected β-amino aldehydes from allylic amines or linear allylic alcohols is described. Here the Pd(II)-catalyzed oxidation of N-protected allylic amines with benzoquinone is achieved in tBuOH under ambient conditions with excellent selectivity toward the anti-Markovnikov aldehyde products and full retention of configuration at the allylic carbon. The method shows a wide substrate scope and is tolerant of a range of protecting groups. Furthermore, β-amino aldehydes ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…A methyl ketone was successfully installed in compounds containing both the isoquinolone and pyrrolopyrazinone ring systems. We then turned our attention to the possible aldehyde‐selective Wacker‐type alkene oxidation developed by Feringa and Grubbs et al . Using silver nitrite and copper(II) chloride as co‐catalysts resulted in formation of the expected aldehyde as the major product in a modest overall yield consistent with the yields reported for these two processes in isolation ( 5 to 7 ) .…”
Section: Figuresupporting
confidence: 59%
See 1 more Smart Citation
“…A methyl ketone was successfully installed in compounds containing both the isoquinolone and pyrrolopyrazinone ring systems. We then turned our attention to the possible aldehyde‐selective Wacker‐type alkene oxidation developed by Feringa and Grubbs et al . Using silver nitrite and copper(II) chloride as co‐catalysts resulted in formation of the expected aldehyde as the major product in a modest overall yield consistent with the yields reported for these two processes in isolation ( 5 to 7 ) .…”
Section: Figuresupporting
confidence: 59%
“…An isotopic labeling study suggested the alkene heteroallylation process proceeds via an isohypsic mechanism involving a somewhat unusual β‐halide elimination step . Here, we describe the development of an isohypsic‐redox sequence (IRS) based on the unification of alkene heteroallylation with transformative Pd‐catalyzed redox‐active processes such as the Suzuki–Miyaura coupling, Buchwald–Hartwig amination, and both the Wacker and Feringa–Grubbs aldehyde‐selective Wacker oxidation protocols (Figure c) . This IRS approach enhances molecular complexity by generating three new bonds in a single process while also forming a heterocycle and a new sp 3 –sp 3 C−C bond.…”
Section: Figurementioning
confidence: 99%
“…Thus,o wing to their stronger oxidizing ability,e lectronwithdrawing-substituted iodine(III) reagents would favor Pd II regeneration and perhaps accelerate the process.T his prediction is opposite to the observation;2)the typical chelating effect on the nucleopalladation reaction of 1b causes it to favor the C1 position, as proposed by Feringa (Scheme 3c, right), [16] and result in predominant formation of the opposite regioisomer to 2b;3)oxypalladation processes typically favor electron-deficient alkenes, [17] whereas the iodine(III)-mediated reactions take place selectively at electron-rich alkene centers. [7] Thes elective formation of syn-5g (Table 3) and honausin C( Scheme 2b)e xemplifies this significant difference.…”
Section: Communicationsmentioning
confidence: 76%
“…Further optimization, involving exclusion of water from the reaction system, increased nitromethane concentration, and even a reduction in catalyst loading, resulted in very high selectivity for aldehyde formation (36:1 aldehyde/ketone) in high yield (77 %; Figure e). Since the use of t BuOH has been established as a strategy to enhance aldehyde selectivity in Wacker‐type oxidations, the importance of the nitrite catalyst and nitromethane as a cosolvent was assessed. Elimination of these components from the optimized reaction conditions led to diminished aldehyde selectivity (8:1 aldehyde/ketone) and formation of defluorination products (Figure f)…”
Section: Methodsmentioning
confidence: 99%